Modeling of Magnetizing Inrush and Internal Faults for Three-phase Transformers - Mohammad Bakhshipour; Farhad Namdari; Mohammad Sedaghat (Institute of Advanced Engineering and Science, 2016)
Among the most noticeable root causes of improper performance in power transformers, internal short circuit faults can be noted and if not quickly be identified and addressed in the accepted time interval, irrecoverable damages such as interruption or even collapse of the network connected to the power transformer would happen. In this contribution, three-phase transformer behaviors under magnetizing inrush, internal short circuit condition and their current values determination have been surveyed using electromagnetic coupling model approach and structural finite element method. Utilizing the definition of transformer in the form of multi-coil and their electromagnetic and electric couple, a three dimensional geometric model of transformer is developed which includes nonlinear characteristics of the transformer, different states of normal and under internal short circuit occurrence and the moment of magnetizing inrush creation are investigated. The comparison between obtained results of presented model simulation with the consequences of practical studies on a typical three phase transformer reveals that the proposed model has a reliable accuracy in detection and modelling the transformer behavior in normal conditions, magnetizing inrush and different types of internal faults. The proposed approach represents an accurate model of a three-phase transformer for protection aims.